Application of Laplace Transform For Solving Population Growth and Decay Models. - Natukunda, Pamellah (Kabale University, 2024)
This study is about the application of Laplace Transform for solving population growth and decay models. It is majorly concerned with the linearity property of the Laplace transform, How the Laplace transform is used in solving population growth and decay model, and How the Laplace transform is used in solving population growth and decay models demonstrated. Laplace can be used to convert complex differential equations to a simpler form having polynomials, convert derivatives into multiple domain variables, and then convert the polynomials back to the differential equation using the Inverse Laplace transform, telecommunication field to send signals to both sides of the medium. For example, when the signals are sent through the phone they are first converted into a time-varying wave and then superimposed on the medium and for many engineering tasks such as Electrical Circuit Analysis, Digital Signal Processing, and System Modelling. The given application shows the effectiveness of the Laplace transform for solving population growth and decay problems. The proposed scheme can be applied for compound interest and heat conduction problems. I encourage mathematicians to use the Laplace transform model in solving differential equations and population models since it is perfect and easy to solve.